Coordinated control to achieve stability and dynamic response enhancement of weak‐grid‐connected inverters based on sequence‐admittance models. Issue 2 (13th November 2021) - Yu, Yanxue; Zheng, Xuemei; Li, Haoyu; Guerrero, Josep M.; Akhavan, Ali
Abstract: In grid‐connected inverters (GCIs), the phase‐locked loop (PLL) behaves as a negative admittance at the point of common coupling (PCC), composed of both the PLL controller and current controller terms. Therefore, not only the PLL dynamics, but also dynamical interactions between the PLL controller and current controller might trigger instabilities in weak grids, which complicates the controller parameters regulation. The smaller PLL bandwidth could help to mitigate the instabilities, but at the expense of sacrificing the system dynamic response. In view of this, a coordinated control composed of the q ‐axis voltage and PCC‐voltage feedforward based on sequence‐admittance models is proposed here. The q ‐axis voltage feedforward is designed with a simple proportional feedforward coefficient to make the PLL‐induced negative admittance insensitive to the PLL controller parameters. In other words, the PLL bandwidth would not be limited by the stability requirements and the dynamic response speed could be ensured. Furthermore, the PCC‐voltage feedforward is developed to coordinate the q ‐axis voltage feedforward by phase compensation, thus to achieve stability improvement. Finally, simulations and hardware‐in‐the‐loop tests are carried out to verify the enhanced stability and dynamic response of the modified GCI with the proposed coordinated control in weak grid.